KOMPARASI ESTETIK SENI GRAFFITI KARYA ALIASTIGA - Siti Hanifah Muslimah; Muh Faisal; M. Muhlis Lugis (Program Studi Pendidikan Seni Rupa Fakultas Keguruan dan Ilmu Pendidikan Universitas Muham, 2023)
This study aims to analyze aesthetic comparisons of graffiti art by Aliastiga from 2006-2022 in Makassar City. The analytical method used in this study is a qualitative descriptive analysis method, supported by the theory of Form Aesthetics from Dr. A.A.M Djelantik and the theory of Functional Aesthetics from Edmund Burke Feldman as a reference for analysis. The results of this study show that the graffiti artwork created by Aliastiga initially originated from an interest in art in the form of a character and writing. The work produced by Aliastiga from early 2006 has shown that artists are very talented and have good skills. Although in reviewing the weight of his work, Aliastiga does not have ideas and messages in his work, Aliastiga emphasizes artistic visuals in his work. Aliastiga graffiti art is not just a hobby, but in it becomes an artistic movement that tends to fight acts of vandalism.